Clinical relevance of Küttner tumour and IgG4‐related dacryoadenitis and sialoadenitis. (25th June 2014) - Furukawa, S; Moriyama, M; Kawano, S; Tanaka, A; Maehara, T; Hayashida, J‐N; Goto, Y; Kiyoshima, T; Shiratsuchi, H; Ohyama, Y; Ohta, M; Imabayashi, Y; et al.
<x xml:space="preserve">Abstract</x> Objectives Küttner tumour (KT), so‐called chronic sclerosing sialoadenitis, is characterised by concomitant swelling of the submandibular glands secondary to strong lymphocytic infiltration and fibrosis independent of sialolith formation. However, recent studies have indicated that some patients with KT develop high serum levels of IgG4 and infiltration of IgG4‐positive plasma cells, namely IgG4‐related dacryoadenitis and sialoadenitis (IgG4‐DS), so‐called Mikulicz's disease. The aim of this study was to clarify the clinical and pathological associations between KT and IgG4‐DS. Materials and Methods Fifty‐four patients pathologically diagnosed with KT or chronic sialoadenitis were divided into two groups according to the presence or absence of sialolith (KT‐S (+) or KT‐S (−), respectively). Results There were no significant differences in the clinical findings, including the mean age, sex and disease duration, between the two groups. All patients in the KT‐S (+) group showed unilateral swelling without infiltration of IgG4‐positive plasma cells or a history of other IgG4‐related diseases (IgG4‐RD), while those in the KT‐S (−) group showed bilateral swelling (37.5%), strong infiltration of IgG4‐positive plasma cells (87.5%) and a history of other IgG4‐RD (12.5%). Conclusions These results suggest an association between the pathogeneses of KT‐S (−) and IgG4‐DS, but not KT‐S (+).